Stimulation of Alpha7 Nicotinic Acetylcholine Receptor Attenuates Nicotine-Induced Upregulation of MMP, MCP-1, and RANTES through Modulating ERK1/2/AP-1 Signaling Pathway in RAW264.7 and MOVAS Cells - Liu, Liping; Wu, Hongxian; Cao, Qunan; Guo, Zhenzhen; Ren, Anmin; Dai, Qiuyan (Mediators of Inflammation, 2017)
Vagus nerve stimulation through alpha7 nicotine acetylcholine receptors (α7-nAChR) signaling had been demonstrated attenuation of inflammation. This study aimed to determine whether PNU-282987, a selective α7-nAChR agonist, affected activities of matrix metalloproteinase (MMP) and inflammatory cytokines in nicotine-treatment RAW264.7 and MOVAS cells and to assess the underlying molecular mechanisms. RAW264.7 and MOVAS cells were treated with nicotine at different concentrations (0, 1, 10, and 100 ng/ml) for 0–120 min. Nicotine markedly stimulated the phosphorylation of extracellular signal-regulated kinase1/2 (ERK1/2) and c-Jun in RAW264.7 cells. Pretreatment with U0126 significantly suppressed phosphorylation of ERK1/2 and further attenuated nicotine-induced activation of c-Jun and upregulation of MMP-2, MMP-9, monocyte chemotactic protein- (MCP-) 1, and regulated upon activation normal T cell expressed and secreted (RANTES). Similarly, nicotine treatment also increased phosphorylation of c-Jun and expressions of MMP-2, MMP-9, MCP-1, and RANTES in MOVAS cells. When cells were pretreated with PNU-282987, nicotine-induced activations of ERK1/2 and c-Jun in RAW264.7 cells and c-Jun in MOVAS cells were effectively inhibited. Furthermore, nicotine-induced secretions of MMP-2, MMP-9, MCP-1, and RANTES were remarkably downregulated. Treatment with α7-nAChR agonist inhibits nicotine-induced upregulation of MMP and inflammatory cytokines through modulating ERK1/2/AP-1 signaling in RAW264.7 cells and AP-1 in MOVAS cells, providing a new therapeutic for abdominal aortic aneurysm.